2020
DOI: 10.1111/acem.14149
|View full text |Cite
|
Sign up to set email alerts
|

Does Intravenous Acetaminophen Reduce Opioid Requirement in Pediatric Emergency Department Patients With Acute Sickle Cell Crises?

Abstract: Objective We evaluated the ability of intravenous (IV) acetaminophen to reduce the amount of opioid medication administered in pediatric patients with sickle cell disease (SCD) having vasoocclusive crisis (VOC) in an emergency department (ED) setting. Methods This was a prospective, randomized, double‐blind placebo‐controlled trial at an academic urban pediatric ED. Participants included patients with SCD, aged 4 to 16 years, with VOC pain. All patients received a 0.1 mg/kg dose of IV morphine, 0.5 mg/kg ketor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The authors reported a mean reduction in pain scores of 2.4 in their analysis of administered IV APAP doses without a concomitant analgesic (total of 49 doses). In an another study, Dhebaria et al 70 conducted an RCT with pediatric patients admitted with a VOC to an academic urban ED. Seventy-one patients were randomized to receive either 0.1 mg/kg of IV morphine, 0.5 mg/kg ketorolac, or both along with 15 m/kg of IV APAP or placebo.…”
Section: Methodsmentioning
confidence: 99%
“…The authors reported a mean reduction in pain scores of 2.4 in their analysis of administered IV APAP doses without a concomitant analgesic (total of 49 doses). In an another study, Dhebaria et al 70 conducted an RCT with pediatric patients admitted with a VOC to an academic urban ED. Seventy-one patients were randomized to receive either 0.1 mg/kg of IV morphine, 0.5 mg/kg ketorolac, or both along with 15 m/kg of IV APAP or placebo.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a number of biopharmaceuticals have been used, including pregabalin [10], montelukast [11], voxelotor [12], crizanlizumab [13], morphine [14][15][16], ketamine [14][15], and ticagrelor [17]. Finally, not surprisingly, pain relievers such as diclofenac [18] and acetaminophen [18][19] have been routinely prescribed.…”
Section: Current Approachesmentioning
confidence: 99%